2020
DOI: 10.1007/s13205-020-02406-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential mRNA panels for severe acute respiratory syndrome coronavirus 2 (COVID-19) diagnosis and treatment using microarray dataset and bioinformatics methods

Abstract: The goal of the present investigation is to identify the differentially expressed genes (DEGs) between SARS-CoV-2 infected and normal control samples to investigate the molecular mechanisms of infection with SARS-CoV-2. The microarray data of the dataset E-MTAB-8871 were retrieved from the ArrayExpress database. Pathway and Gene Ontology (GO) enrichment study, protein-protein interaction (PPI) network, modules, target gene-miRNA regulatory network, and target gene-TF regulatory network have been performed. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 198 publications
(214 reference statements)
0
35
0
Order By: Relevance
“… India To understand the mechanisms of SARS-CoV-2 infection and identify potential novel diagnostic or therapeutic targets through bioinformatics analysis including miRNA regulatory networks. ( Vastrad et al, 2020 ) 21 Maitra A June 4, 2020. India To provide information on the prevalence of different viral SARS-CoV-2 clades regional differences and potential human miRNA binding sites affected by mutations of the virus by sequencing the SARS-CoV-2 genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… India To understand the mechanisms of SARS-CoV-2 infection and identify potential novel diagnostic or therapeutic targets through bioinformatics analysis including miRNA regulatory networks. ( Vastrad et al, 2020 ) 21 Maitra A June 4, 2020. India To provide information on the prevalence of different viral SARS-CoV-2 clades regional differences and potential human miRNA binding sites affected by mutations of the virus by sequencing the SARS-CoV-2 genome.…”
Section: Resultsmentioning
confidence: 99%
“… miR-922 PI3 GO molecular function: endopeptidase inhibitor activity, peptidase inhibitor activity, endopeptidase regulator activity Taz et al, 2020 , PDCD1 This protein was found upregulated in SARS-CoV-2 infected samples. Vastrad et al, 2020 . KEGG pathways: T cell receptor signaling pathway, Adaptative Immune system GO: regulation of immune system process, T cell activation, leukocyte activation, cell activation miR-326 S100A8 Go biological process: leukocyte aggregation, defense response to fungus, neutrophil chemotaxis, granulocyte chemotaxis, neutrophil migration Taz et al, 2020 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been demonstrated by the clinical responses to the COVID-19 pandemic, patient risk stratification can be a powerful tool in informing optimal resource management practices (staffing, therapeutics, etc.) [ 73 , 74 ]. In a second scenario, these miRNAs could be used for monitoring convalescent EVD patients for signs of long-term disease sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…SNX-5422 dampened expression of cellular genes, previously shown to be associated with SARS-CoV-2 -mediated proinflammatory response and hyper-cytokinemia (Figure 3B). Specifically, these inflammatory genes could be broadly categorized into chemokines ( CXCL1 (Coperchini et al, 2020) , CXCL5 (Coperchini et al, 2020) , CXCL6 (Blanco-Melo et al, 2020) , CXCL3 (Blanco-Melo et al, 2020) and CXCL2 (Zhou et al, 2020a)), chemokine-receptor ligands ( CCL20 (Zhou et al, 2020a) , CX3CL1 (Nienhold et al, 2020)), cytokines ( IL36G (Xiong et al, 2020)), interleukins ( IL-19 (Vastrad et al, 2020) , CXCL8 (Zhou et al, 2020a) , IL-32 (Blanco-Melo et al, 2020)), tumor necrosis factor alpha-induced protein ( TNFAIP2 (Fagone et al, 2020)), regulators of inflammatory responses ( CSF3 (Nunnari et al, 2020) , S100A8 (Zhou et al, 2020a) , S100A9 (Zhou et al, 2020a) , SCGB3A1 (Mick et al, 2020) , S100A2 (Xu et al, 2020)) and interferon-induced proteins ( RSAD2 (Zhou et al, 2020a), IFI44L (Mick et al, 2020), IFITM1 (Zhou et al, 2020a) , MX2 (Lieberman et al, 2020), IFI27 ( Mick et al, 2020) , ISG15 (Zhou et al, 2020a) ). Collectively, our analysis suggests that early treatment with SNX-5422 may mitigate SARS-CoV-2-mediated hyperinflammation, thereby improving clinical outcomes of COVID-19.…”
Section: Resultsmentioning
confidence: 99%